KNM 1638 - A High Yielding Gall Midge Resistant Early Duration PJTSAU Rice (Oryza sativa L.) Variety Suitable for Telangana State - Siddi, Sreedhar; Raju, Ch. Damodar; Chandramohan, Y.; Rani, T. Shobha; Rao, V. Thirumala; Omprakash, S.; Varma, N. Rama Gopala; Jagadeeshwar, R.; Babu, T. Kiran; Anil, D.; Sreedhar, M.; Umareddy, R.; et al. (International Journal of Bio-resource and Stress Management, 2022)
The promising high yielding rice genotype, KNM 1638 is a medium slender, early duration (120–125 days) and photo insensitive culture with high yield potential (7356 kg ha-1) having resistance to gall midge and leaf blast, and moderately resistant to neck blast with better adaptability. This rice culture KNM 1638, a derivative of the cross JGL 11727×JGL 17004 was released through State Varietal Release Committee on the name of Kunaram Vari 2 for Telangana state during the year 2021 as an alternate variety to BPT 5204. It has semi-dwarf plant type with moderate tillering, semi-erect flag leaf, all plant parts green, semi-compact well exerted semi-erect attitude of branching panicle, straw-colored awn less grains and its grain classified as a translucent medium slender grain. In the overall performance, KNM 1638 recorded mean productivity of 7356 kg ha-1 in the eight years of trials with 12.8% increase over the check varieties. It has good grain, cooking and eating quality, and good marketing facility as quality-wise it recorded 63% head rice recovery and 21.47% amylose content with soft gel consistency and moderate gelatinization temperature. The rice variety, KNM 1638 is suitable for cultivation during kharif, late kharif and rabi seasons throughout Telangana State with higher yield, better pest and disease resistance and good cooking quality in comparison to the check varieties.